TIM4+macrophages suppress the proinflammatory response to maintain the chronic alveolar echinococcosis infection - Wang, Liang; Liu, Yumei; Ma, Yuyu; Zhou, Xuan; Aibibula, Maidinaimu; Zhang, Xue; Zhao, Hui; Zhou, Jinping; Tian, Fengming; Ma, Xiumin (Frontiers in Cellular and Infection Microbiology, 2025)
BackgroundAlveolar echinococcosis (AE), a severe zoonotic disease predominantly endemic to pastoral regions, is characterized by hepatic parasitic lesions caused by Echinococcus multilocularis.MethodsThis study investigated the role of T-cell immunoglobulin and mucin domain-4 (TIMD4/Tim-4) in patients with hepatic AE. In total, 129 patients were enrolled from the First Affiliated Hospital of Xinjiang Medical University between 1 March 2018 and 1 March 2021. Histological, genetic, and serological tests were employed to evaluate Tim-4 and inflammatory cytokine expression. The liver immune microenvironment at the middle and late stages of mice infected with E. multilocularis was established in vitro to assess cytokine dynamics and liver fibrosis biomarkers.ResultsClinical analysis revealed the upregulation of Tim-4 within the hepatic lesions of patients with AE, with its expression spatially localized to macrophage-enriched regions and functionally linked to extracellular inflammatory modulation. Meanwhile, the liver tissues of the patients had characteristic pathological changes in the vesicles and progressive fibrotic remodeling, concurrent with a significant suppression of proinflammatory cytokine activity. Tim-4+ macrophages inhibited the release of proinflammatory cytokines at the middle and late stages of E. multilocularis infection to maintain immune tolerance, and inhibition of Tim-4 expression may even reverse the level of liver fibrosis in vitro.ConclusionsTim-4 attenuated the predominant proinflammatory response, thereby facilitating immune evasion by E. multilocularis. Notably, inhibition of Tim-4 in macrophages not only restored the inflammatory balance but also significantly reversed hepatic fibrotic progression.